A Misconception Analysis of Buffer Material using Three Tier Multiple Choice Test assisted by CBT for SMAN 9 Semarang - Septian, Ifandika Dwi; Susilaningsih, Endang; Susilogati Sumarti, Sri (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
Student learning outcomes are still low. Students have an average score below KKM. KKM is determined by each school. KKM in SMAN 9 Semarang is 70. The low value of KKM is caused by students not yet mastering the prerequisite material acid-base. Based on these data student?s misconception need to be analyzed. This study aims to analyze the misconception of buffer material on students. The type of  this research is mixed method. The research design used was a sequential explanatory. The research procedure is following the mixed method syntax. The sample in this study were 128 students from SMAN 9 Semarang. Quantitative data were collected using 10 three-tier multiple choice test questions that used the student?s reasons and level of confidence. The validation results of the test questions are valid and reliable. Qualitative data was collected by interviewing students. The results showed that students have scientific knowledge 16%, type 1 misconception 19%, type 2 misconception 22%, type 3 misconception 37%, lucky 1%, lack of knowledge type 1 1% concept, lack of knowledge type 2 1% concept, and lack of knowledge type 3 3%.